Analysis of Leadership Techniques of Principal of SD Plus Mutiara Insani - Prajna Hewu Wau Pamalungan; Eka Prihatin; Diding Nurdin (Didaktika: Jurnal Kependidikan, 2024)
This research discusses how the leadership style of a democratic principal. The purpose of this research is to describe the leadership style of the principal of SD Plus Mutiara Insani. The benefits of this research are twofold; theoretical benefits; providing new information in education, especially management by school principals in improving the quality of education reflected in the quality of schools. and practical benefits; helping school principals reveal the level of success position of SD Plus Mutiara Insani. This type of research is descriptive qualitative. Data collection techniques were carried out by observation, interviews, and documentation. The interviewees in this study were teachers, principals, and vice principals of the curriculum section. Data analysis techniques are carried out through four stages which include: data collection, data reduction, data presentation, and conclusion drawing/verification. Data validity. The results showed that the principal's leadership style at SD Plus Mutiara Insani is implemented according to the criteria of a democratic leader, namely involving subordinates in deliberations to improve the quality of education and establishing better communication for formal and informal relationships. The principal also always treats and satisfies the needs of his subordinates fairly. With this leadership style, the school can have adequate capabilities.